Identifying EFL Students Speaking Performance: Foreign Language Anxiety Among Non-English Department Students - Satrio Binusa Suryadi; Faiz Ushbah Mubarok; Asri, Atiqah Nurul; Ulfa, Farida; Usman Nurhasan; Anugrah Nur Rahmanto; Risa Juliadilla (Universitas Terbuka, 2024)
EFL learners at the tertiary level continue to struggle to understand English, especially when speaking. Certain elements become hurdles when students talk. The variables are referred to as foreign language anxiety. This phenomenon was produced by worry that interfered with students' performance: communication apprehension, fear of poor evaluation, and low self-esteem. This study employed a qualitative method with a case study methodology. The data was gathered via a questionnaire and a semi-structured interview with a non-English department student at the State Polytechnic of Malang. The questionnaire was based on Horwitz's foreign-language classroom anxiety scale. The findings of this study revealed that the most important aspects influencing student performance are avoiding mistakes that lead to poor evaluation. Suggestions for learners, that they would be more readily to speak when they get support by the new technology